IMPLEMENTASI PERATURAN PEMERINTAH NO. 16 TAHUN 2007 TENTANG PENYELENGGARAAN KEOLAHRAGAAN DI PEMERINTAH DAERAH DALAM PEMBINAAN OLAHRAGA CABANG SEPAK BOLA DI KABUPATEN MALANG (Studi di Dinas Pemuda dan Olahraga Kabupaten Malang) - ODDIE BAYU O.R. (Kumpulan Jurnal Mahasiswa Fakultas Hukum, 2014)
AbstractThe author here discusses about the implementation of Government Regulation . 16 of 2007 are in this set of sports coaching in local governance rather, here the author discusses about coaching in the sport of football The purpose of the author discusses rather than the Government Regulation No. 16 Such as to know the missing link of our sport development system more precisely or sports especially football . The studies were performed by the type here is studies of empirical research in which researchers examined samples using techniques and interviews with relevant parties involved in the sports system in local government then , analyzed in accordance with the laws and regulations that exist and then drawn conclusions relating the problems examined whether local governments are already implementing poor districts using the correct Law The results of research conducted by the authors is that in terms of implementation of government 's role in coaching the sport , especially in football branch minim.tidak still ongoing guardianship , as well as cooperation or coordination between the government and the institutions that have been established , in this is KONI to Breeding and football athletes themselves to current sports -related agencies and organizations not implementing Regulation No. 16 of 2007 in which the stakeholders are still using the Law No. 5 Year 2005 concerning the sports system in which it resulted in the interpretation of the extent of implementation of the method sports coaching , especially in this branch of the sport of football itself Improve facilities and infrastructure , as well as sports equipment fittings , as one of the supporting factors and implemented to attain the ideals of sports in general , especially in the martial sport of football . As well as the implementation of the legislation will allow better targeted organization in this district particularly unfortunate KONI , Department of Youth and Sports and the PSSI will facilitate and provide maximum results for the achievement of objectives in this regard in terms of coaching the sport of football